EFFECT OF LEVERAGE AND FIRM SIZE ON COMPANY VALUE WITH EXCHANGE RATE AND HEDGING DECISION AS MODERATION VARIABLE (CASE STUDY ON NON-FINANCIAL COMPANIES LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2017-2018) - Fira Majdina Siswanto; Rika Promalessy; Fitri Fitri (Universitas Riau, 2021)
In general, the value of a company is a description of the condition of the company, whether it is in good condition or not. In this research, exchange rates and hedging are moderating variables for various variables that affect company value, namely leverage and firm size variables. The purpose of this research is to determine the effect of each variable on firm value in non-financial companies on the Indonesia Stock Exchange in 2017-2018. The sampling technique used was purposive sampling with the amount of 285 companies. The research hypothesis was tested by using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results show that the exchange rate can moderate the leverage and firm size on firm value, hedging cannot moderate the leverage but can moderate the firm size on firm value.